The subjective health of adults in Germany - Thomas Lampert; Claudia Schmidtke; Lea-Sophie Borgmann; Christina Poethko-Müller; Benjamin Kuntz (Journal of Health Monitoring, 2018)
The term ‘subjective health’ reflects not only existing illnesses and health complaints, but particularly emphasizes the personal well-being. Studies often collect data on subjective health by asking participants to provide self-assessments of their general state of health. This was also the case with GEDA 2014/2015-EHIS, which employed the internationally renowned Minimum European Health Module (MEHM) as part of the study. Its results demonstrate that 68.2% of adults in Germany rate their general health as very good or good, with the remaining 31.8% rating it as fair, poor or very poor. The proportion of women who rate their general health as very good or good is slightly lower than the proportion of men who do so (66.6% compared to 69.9%). With increasing age, women and men view the condition of their general health as worsening. The study also identified educational differences which showed that men and women with low levels of education tend to rate their health worse compared to self-assessments provided by women and men with higher levels of education, and in some cases also regional differences.